Memperkenalkan Scrum Sebagai Kerangka Kerja Perusahaan Demi Memenuhi Tantangan Perubahan Pasar Di Era Revolusi Industri 4.0 Yang Dinamis - Ni Putu Diah Untari Ningsih (Jayapangus Press, 2020)
The digital era of the dynamic industrial revolution 4.0, requires companies to quickly innovate to make products that can meet the needs of consumers and released in a short time. This method is to answer the company's efforts to stay ahead of competitors. Building software requires a framework to facilitate the planning, development and maintenance. The Scrum method can be used as a framework for developing software interoperability with a faster time (Agile). Scrum was made by Jeff Sutherland and Ken Schwaber, who was a developer in the mid-1990s in America. Thanks to this finding, it can lead technology companies like Amazon, Google, and Facebook to become giants until now. The Scrum method has a work pattern of breaking jobs into smaller tasks (tasks) and is distributed among the Development Team on a regular basis in a short cycle of time so that system development can be completed quickly. Scrum is recommended for project types that are not deadline oriented, with creative and high-quality product targets. Because Scrum's focus is on the process, with iteratives and targets per Sprint, it is hoped that each piece of product will be better than the previous Sprint. The advantages of the Scrum method in this study such as the work pattern of breaking work into tasks that are evenly distributed to all development teams to be completed in a fast work cycle requires excessive accuracy in determining the Backlog.